2005
DOI: 10.1902/jop.2005.76.8.1374
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives and Periodontal Diseases: Rethinking the Association Based Upon Analysis of National Health and Nutrition Examination Survey Data

Abstract: This analysis failed to validate the theory that earlier high- or current low-dose OC use is associated with increased levels of gingivitis or periodontitis and suggests an important reexamination of the perceived association between OC use and periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
1
29
1
2
Order By: Relevance
“…In this study, there was no statistically significant positive correlation between the clinical parameters analyzed the total duration of oral contraceptive intake. These findings can be explained by the low hormonal dosage of the current oral contraceptive formulations used by the patients selected in this study, in agreement with other results obtained with women taking low-dose oral contraceptives, which found no statistically significant differences in the clinical parameters 20,23 . However these results are contradictory as it has been observed that women taking COC with low hormonal dosage present greater periodontal inflammation, greater PD and loss of attachment than women not taking these medications 16 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, there was no statistically significant positive correlation between the clinical parameters analyzed the total duration of oral contraceptive intake. These findings can be explained by the low hormonal dosage of the current oral contraceptive formulations used by the patients selected in this study, in agreement with other results obtained with women taking low-dose oral contraceptives, which found no statistically significant differences in the clinical parameters 20,23 . However these results are contradictory as it has been observed that women taking COC with low hormonal dosage present greater periodontal inflammation, greater PD and loss of attachment than women not taking these medications 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Clinical studies reported higher prevalence of gingival inflammation, loss of attachment and gingival enlargement in woman taking hormone-based oral contraceptives 8,10,19,21 . However, recent studies based on large 23 or small 20 population samples suggested that current combined oral contraceptives (COC) do not affect periodontal health, possibly related to their lower concentration of progesterone and estradiol than previously used medications 16 . Gingival inflammation seems to be associated to high concentrations of sex hormones present in COC 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent small-scale clinical study found no association between the use of low-dose oral contraceptives and gingivitis, but the relationship between OCs and periodontal diseases has yet to be investigated in a large representative population-based sample. A crosssectional study in premenopausal women found no association between previous high-dose www.intechopen.com or current low-dose oral contraceptive intake and increased levels of gingivitis or periodontitis, emphasizing the need for a reexamination of the perceived association between these drugs and periodontal diseases (Taichman & Eklund, 2005).…”
Section: Gingivitis Associated With Oral Contraceptivesmentioning
confidence: 99%
“…En un estudio de 2004 se evaluó la influencia de los anticonceptivos orales en la salud gingival y periodontal (22), ya que la tendencia clásica era la de relacionar dichos fármacos con las enfermedades gingivales (23).…”
Section: Gingivitis Influidas Por Drogasunclassified
“…En un estudio de 2005, tomando datos de las encuestas epidemiológicas NHANES (Nacional Health and Nutrition Examination Survey), se intentó confirmar la asociación entre los ACO y las enfermedades periodontales usando para ello el análisis de regresión logística (22). Los autores del estudio encontraron asociaciones entre los ACO y la gingivitis, pero en cualquier caso no fueron estadísticamente significativas, por lo que, según los autores del artículo, no puede decirse que las dosis actuales de ACO, ni las antiguas, estén asociadas con una mayor tasa de enfermedad gingival o periodontal, por lo que proponen una revisión de las teorías clásicamente aceptadas.…”
Section: Gingivitis Influidas Por Drogasunclassified